Effect of Hot Extrusion on Electrical Tribological Behavior of Ag-Cu/MoS2 Composite under Air and Vacuum Conditions. Issue 4 (4th July 2017) - Chen, Wu; Wang, Yan; Feng, Chunfang; Zhang, Lei
ABSTRACT: The different microstructures of silver–copper/molybdenum disulfide (Ag-Cu/MoS2 ) composites were manufactured by hot press and hot extrusion processes to investigate the electrical tribological behaviors of both the hot-pressed and hot-extruded composites under air and vacuum. The results showed that microstructures and properties of Ag-Cu/MoS2 composites were improved by hot extrusion, which decreased the wear rates rapidly in both air and vacuum. In air, hot extrusion could improve the transfer layer and tribofilm, resulting in a significant decrease in contact voltage drop, which goes from more than 70 mV in the hot-pressed composite to 30 mV at the hot-extruded composite. Under vacuum condition, some wear debris was melted on the worn surface and then transferred to the counterface to form the transfer layers, which led to the lower contact voltage drops under vacuum, about 6 mV in hot-pressed composites and 3 mV in hot-extruded composites. In addition, the severe adhesive and abrasive wear were attributed to the molten wear debris and transfer layer, resulting in a dramatic fluctuation in the friction coefficient in a vacuum.